A REVIEW ON UNDER WATER WELDING PROCESS - KUMAR, KUNTHLESH; SINGH, RICKRAMJEET (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Welding in offshore and marine application is an area of research and understanding where, many problems are still unsolved. In the present paper, a brief classification of underwater welding is made, the principals involved and the advantages and disadvantages of the various types of underwater welding are described. Further discussion is made over the present conventional and some advanced techniques used. Finally, the scope of further research has been recommended. Welding in offshore and marine application is an area of research and understanding where, many problems are still unsolved. In the present paper, a brief description of the different commercial underwater techniques has been made. The problems in underwater welding have also been discussed in context to the existing welding techniques. Detailed description of a few advanced welding techniques has also been made. Finally, the scope of further research has been recommended